Febrile Seizure Risk After Vaccination in Children 6 to 23 Months - Duffy, Jonathan (Pediatrics, 2016)
BACKGROUND AND OBJECTIVE: An increased risk of febrile seizure (FS) was identified with concomitant administration of trivalent inactivated influenza vaccine (IIV3) and pneumococcal conjugate vaccine (PCV) 13-valent during the 2010–2011 influenza season. Our objective was to determine whether concomitant administration of IIV3 with other vaccines affects the FS risk. METHODS: We examined the risk of FS 0 to 1 day postvaccination for all routinely recommended vaccines among children aged 6 through 23 months during a period encompassing 5 influenza seasons (2006–2007 through 2010–2011). We used a population-based self-controlled risk interval analysis with a control interval of 14 to 20 days postvaccination. We used multivariable regression to control for receipt of concomitant vaccines and test for interaction between vaccines. RESULTS: Only PCV 7-valent had an independent FS risk (incidence rate ratio [IRR], 1.98; 95% confidence interval [CI], 1.00 to 3.91). IIV3 had no independent risk (IRR, 0.46; 95% CI, 0.21 to 1.02), but risk was increased when IIV3 was given with either PCV (IRR, 3.50; 95% CI, 1.13 to 10.85) or a diphtheria-tetanus-acellular-pertussis (DTaP)-containing vaccine (IRR, 3.50; 95% CI, 1.52 to 8.07). The maximum estimated absolute excess risk due to concomitant administration of IIV3, PCV, and DTaP-containing vaccines compared with administration on separate days was 30 FS per 100 000 persons vaccinated. CONCLUSIONS: The administration of IIV3 on the same day as either PCV or a DTaP-containing vaccine was associated with a greater risk of FS than when IIV3 was given on a separate day. The absolute risk of postvaccination FS with these vaccine combinations was small.